On the dynamics of the Ross Gyre: the relative importance of wind, buoyancy, eddies, and the Antarctic Circumpolar Current - Wang, Yang; Chassignet, Eric P.; Speer, Kevin (Frontiers in Marine Science, 2024)
The formation of cold, dense waters south of the Antarctic Circumpolar Current (ACC) is one of the main drivers of the global overturning circulation, with major effects on the earth’s climate. A key region where dense waters are formed is the Ross Sea, which is separated from the ACC by the Ross Gyre. The strength and variability of the Ross Gyre circulation impacts the formation and export of dense water, but observations of the Ross Gyre circulation are limited because of its remote location, severe weather conditions, and ice cover that has limited the application of remote sensing techniques. Quantitative estimates of the gyre’s total strength are difficult to obtain from hydrographic observations alone due to the limited sampling and the relatively weak stratification. In this paper, we use a combination of observations and modeling studies to estimate the strength and variability of the Ross Gyre transport and investigate the relative contributions of the wind, buoyancy forcing, eddy fluxes, and the influence of ACC to the Ross Gyre circulation. We find that the mean transport of the Ross Gyre can be as high as about 45 Sv, more than twice the typical estimate of about 20 Sv. Sensitivity experiments to wind and buoyancy forcing, nonlinear terms, and the ACC were performed with a regional configuration of the Hybrid Coordinate Ocean Model (HYCOM). The numerical experiments show that the total Ross Gyre circulation, and its variability, are primarily wind-driven. The ACC is responsible for a small recirculation. Buoyancy and nonlinearity or eddy fluxes play a smaller role in the gyre dynamics, though they are regionally important.